Simplified protocol for flow cytometry analysis of fluorescently labeled exosomes and microvesicles using dedicated flow cytometer. Issue 1 (31st March 2015) - Pospichalova, Vendula; Svoboda, Jan; Dave, Zankruti; Kotrbova, Anna; Kaiser, Karol; Klemova, Dobromila; Ilkovics, Ladislav; Hampl, Ales; Crha, Igor; Jandakova, Eva; Minar, Lubos; Weinberger, Vit; et al.
Abstract : Flow cytometry is a powerful method, which is widely used for high‐throughput quantitative and qualitative analysis of cells. However, its straightforward applicability for extracellular vesicles (EVs) and mainly exosomes is hampered by several challenges, reflecting mostly the small size of these vesicles (exosomes: ~80–200 nm, microvesicles: ~200–1, 000 nm), their polydispersity, and low refractive index. The current best and most widely used protocol for beads‐free flow cytometry of exosomes uses ultracentrifugation (UC) coupled with floatation in sucrose gradient for their isolation, labeling with lipophilic dye PKH67 and antibodies, and an optimized version of commercial high‐end cytometer for analysis. However, this approach requires an experienced flow cytometer operator capable of manual hardware adjustments and calibration of the cytometer. Here, we provide a novel and fast approach for quantification and characterization of both exosomes and microvesicles isolated from cell culture media as well as from more complex human samples (ascites of ovarian cancer patients) suitable for multiuser labs by using a flow cytometer especially designed for small particles, which can be used without adjustments prior to data acquisition. EVs can be fluorescently labeled with protein‐(Carboxyfluoresceinsuccinimidyl ester, CFSE) and/or lipid‐ (FM) specific dyes, without the necessity of removing the unbound fluorescent dye by UC, which further facilitates and speeds up the characterization of microvesicles and exosomes using flow cytometry. In addition, double labeling with protein‐ and lipid‐specific dyes enables separation of EVs from common contaminants of EV preparations, such as protein aggregates or micelles formed by unbound lipophilic styryl dyes, thus not leading to overestimation of EV numbers. Moreover, our protocol is compatible with antibody labeling using fluorescently conjugated primary antibodies. The presented methodology opens the possibility for routine quantification and characterization of EVs from various sources. Finally, it has the potential to bring a desired level of control into routine experiments and non‐specialized labs, thanks to its simple bead‐based standardization.